Understanding climate-smart nutritious food: the role of home-grown school feeding programs in creating demand - Hunter, Danny (2024)
Presented at the Global Child Nutrition Forum in Osaka, Japan, 9-12 December 2024. Using examples from Brazil, Kenya, and Micronesia, this presentation explores how home-grown school feeding programs can create demand for climate-smart nutritious foods such as neglected and underutilized species of fruits and vegetables.